Influence of a bimetallic shell and rotation on the interaction of a striker with a metal-ceramic semi-infinite barrier - Radchenko, Pavel Andreyevich; Batuev, Stanislav Pavlovich; Radchenko, Andrey Vasil′yevich (Computational Continuum Mechanics, 2025)
The high-velocity impact of a striker, composed of a high-strength steel core, a lead filler and a brass shell, on metal-ceramic and monolithic metal barriers is numerically modelled. The metal-ceramic barrier is a two-layer structure, with the upper layer made of boron carbide (B4C) ceramics and the lower layer made of aluminum. The monolithic barrier consists entirely of aluminum. The interaction angles between the striker’s longitudinal axis and the normal to the barrier, ranging from 0 to 45 degrees, are considered. The influence of the bimetallic shell and the striker’s rotation around its longitudinal axis on its interaction with a barrier is investigated. The behavior of metallic materials and B4C ceramics is described using an elastic-plastic model. The fracture criterion for metallic materials is defined by a plastic strain limit. For ceramics, a deformation criterion is applied, considering both compressive and tensile strengths. The modeling is performed within a three-dimensional finite element framework using the EFES 2.0 software, which is capable of simulating body fragmentation, formation of new contact and free surfaces, and material erosion. The full-scale experimental data are in good agreement with the computational results, which confirms the adequacy of the mathematical model and numerical algorithm. The numerical method permits a parametric study of the influence of kinematic, geometric and structural factors on the interaction process. It is shown that the bimetallic shell and the striker’s rotation have a significant effect on its interaction with the metal-ceramic barrier.